The European Registry for Patients with Mechanical Circulatory Support (EUROMACS): first annual report - de By, Theo M M H; Mohacsi, Paul; Gummert, Jan; Bushnaq, Hasan; Krabatsch, Thomas; Gustafsson, Finn; Leprince, Pascal; Martinelli, Luigi; Meyns, Bart; Morshuis, Michiel; Netuka, Ivan; Potapov, Evgenij; et al. (European journal of cardio-thoracic surgery, 2015)
The European Registry for Patients with Mechanical Circulatory Support (EUROMACS) was founded on 10 December 2009 with the initiative of Roland Hetzer (Deutsches Herzzentrum Berlin, Berlin, Germany) and Jan Gummert (Herz- und Diabeteszentrum Nordrhein-Westfalen, Bad Oeynhausen, Germany) with 15 other founding international members. It aims to promote scientific research to improve care of end-stage heart failure patients with ventricular assist device or a total artificial heart as long-term mechanical circulatory support. Likewise, the organization aims to provide and maintain a registry of device implantation data and long-term follow-up of patients with mechanical circulatory support. Hence, EUROMACS affiliated itself with Dendrite Clinical Systems Ltd to offer its members a software tool that allows input and analysis of patient clinical data on a daily basis. EUROMACS facilitates further scientific studies by offering research groups access to any available data wherein patients and centres are anonymized. Furthermore, EUROMACS aims to stimulate cooperation with clinical and research institutions and with peer associations involved to further its aims. EUROMACS is the only European-based Registry for Patients with Mechanical Circulatory Support with rapid increase in institutional and individual membership. Because of the expeditious data input, the European Association for Cardiothoracic Surgeons saw the need to optimize the data availability and the significance of the registry to improve care of patients with mechanical circulatory support and its potential contribution to scientific intents; hence, the beginning of their alliance in 2012. This first annual report is designed to provide an overview of EUROMACS' structure, its activities, a first data collection and an insight to its scientific contributions.
Keywords: Left ventricular assist device; design vybavení; Europe; Biventricular assist device; Total artificial heart; Evropa; registrace; End-stage heart failure; Equipment Design; Registries; Humans; Bridge to transplant; srdeční selhání; Heart-Assist Devices; Registry; Right ventricular assist device; Heart Failure; lidé; podpůrné srdeční systémy; Mechanical circulatory support